Information-seeking Behavior of Dairy Farmers regarding Prevention of Zoonotic Disease - Ahuja, Rakesh; Gautam,; Sarita,; Rachna,; Singh, Ruchi (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was carried out to ascertain dairy farmers’ information-seeking behavior regarding the prevention of zoonotic diseases.The study was conducted in 8 villages chosen randomly from 2 districts of Haryana state. A majority of the respondents had moderateinformation-seeking behavior about zoonoses. This was assessed in terms of ‘sources of information’ and ‘extent and how frequently theinformation was sought.’ Further, the correlation between the respondents’ personality traits and their information-seeking behaviorscores revealed that different variables like extension participation, social participation, caste, and risk orientation exerted significantinfluence. Most of the time, the sources utilized by the respondents were progressive and co-farmers, followed by veterinary hospitals,neighbors/ friends, training, etc. Respondents sought more information on selection criteria for disease-free animals, storage of feed,supplemental feed preparation, and health care. It is suggested that further studies to understand the factors affecting the informationbehavior of farmers are needed.
Keywords: : Dairy farmers; Haryana; Information-seeking behavior; Zoonoses